COMPARTILHAMENTO DO CONHECIMENTO EM COMISSÕES DE PROCESSO ADMINISTRATIVO DISCIPLINAR: ESTUDO EM UMA UNIVERSIDADE FEDERAL À LUZ DA GESTÃO DO CONHECIMENTO - Martins, Felipe Raphael Marins (2021)
Public universities are environments prone to conflicts, due to the enormous diversity of people, opinions, projects and objectives, which reflect the contradictions of society. In this context, most conflicts become disciplinary administrative proceedings (DBP), which represents the instrument by which the public administration exercises its power duty to investigate functional infractions and impose penalties on its public agents. It happens that, in general and also in the context of the Federal University of Espírito Santo (Ufes), the conduct of these procedures has presented un satisfactory results, generating the accumulation of processes, procedural moratorium, strengthening of the litigant culture and, consequently, inefficiency. The problem lies in the fact that two of the main factors that hinder the development of PADs in public institutions, in general, are the lack of training of the members of disciplinary committees and the small number of employees able to work in them. This fact also occurs in Ufes, allied to an aggravating factor, which is the lack of a reference document for the procedures to be performed by disciplinary committees. In this sense, the main objective of this study was to understand the main needs and difficulties in the performance of the employees who are members of the disciplinary committees at Ufes and to demonstrate how the theory of creation and the sharing of knowledge can collaborate in the solution and mitigation of the difficulties identified. In theoretical terms, the research uses either the Theory of Knowledge Management (CG), specifically the Theory of Knowledge Creation, by Takeuchi and Nonaka (2008), centered on the issue of tacit and explicit knowledge and its importance in the creation and sharing of knowledge and organizational learning. Regarding the methods and procedures, the study adopted the qualitative approach, using scripts of pre-structured interviews to raise the profile of the members of the committees, as well as to identify the difficulties, needs and suggestions of the servants involved in conducting the work in the disciplinary committees. As results, the main needs and difficulties faced by these servers in the management of processes were mapped and, there for propositions of practices and guidelines were made based on the CG to solve/minimize the identified problems. From the results, present orb as technical/technological product the "instructional material: reference for the development of work in disciplinary committees", in order to guide the servers, offer a guiding document for the work carried out by the committees, share knowledge in the institution, minimize risks and increase the effectiveness of this process.